PENGARUH LAYANAN PENGGUNA PERPUSTAKAAN TERHADAP MOTIVASI BELAJAR MAHASISWA PPKN FKIP UNIVERSITAS RIAU ANGKATAN 2013, 2014 DAN 2015 - Gultom, Ester; Hambali, Hambali; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The library is the heart of the university. Because the library at the college has a very important position. Library services should be more attractive, friendly, fast and accurate on the needs of users or students to anticipate developments in technology and information as well as friendly services in order to motivate student learning as the dominant user. From that sense, the nature of the library is a learning resource center and information source for the wearer. Formulation of the problem in this research is: